2014
DOI: 10.1016/s2214-109x(14)70237-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of female human papillomavirus vaccination in 179 countries: a PRIME modelling study

Abstract: WHO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
204
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(211 citation statements)
references
References 19 publications
2
204
1
4
Order By: Relevance
“…Only a few countries in Asian regions, including Nepal, and Malaysia, provide HPV vaccines as national policies (57). This might be caused by several issues, such as lack of Asian-contextspecific evidence on the efficacy of HPV vaccination, socioeconomic barriers, and most importantly, scarce national budgets which hamper implementation of HPV vaccination in most of Asian countries (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few countries in Asian regions, including Nepal, and Malaysia, provide HPV vaccines as national policies (57). This might be caused by several issues, such as lack of Asian-contextspecific evidence on the efficacy of HPV vaccination, socioeconomic barriers, and most importantly, scarce national budgets which hamper implementation of HPV vaccination in most of Asian countries (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…74 Studies in cervical cancer project that given established trends and efficacy, significant decreases in incidence and mortality from cervical cancer would be observed by 2050. 75 Given the higher median age of diagnosis of oropharyngeal cancer compared to cervical cancer (58 vs. 48 years), 76 reduction in incidence and mortality rates for oropharyngeal cancer would not likely be observed until at least 2060. 3 In addition to assumptions regarding vaccine efficacy and vaccine uptake, this projection also assumes sustained vaccine protection and no contribution of the second peak of oral HPV infection seen in older populations.…”
Section: What Do We Know About Hpv Vaccines In Hnscc?mentioning
confidence: 99%
“…85 Even if vaccine efficacy against oral infection or vaccine uptake in men is minimal, herd immunity is likely to play a role in decreasing the overall prevalence of HPV in the general population, though these effects are difficult to estimate. 75 In this changing landscape, there are new challenges in evaluating vaccine efficacy. Placebo-controlled trials can no longer be ethically performed, however, observed changes in current OPC incidence trends can provide indirect evidence for the potential impact of HPV vaccines in OPC.…”
Section: ) Conclusion – What Does the Landscape Look Like Ahead?mentioning
confidence: 99%
“…Lastly, while the financial cost has been the major prohibitive factor to add the vaccine on the national vaccination program [31], more evidence has shown that the vaccine is cost effective compared to the cost of HPV and anogenital cancer treatments and damage to the quality of life [32,33]. In Thailand, the series of HPV vaccines cost between US$ 180 and US$ 340, while the gross national income per capita was approximately US$ 3,900 [33]. Relieving financial burdens of vaccination is necessary.…”
mentioning
confidence: 99%